Efectividad del plasma rico en plaquetas en la cicatrización de heridas postexodoncia - Cantuña Flores, Mario Israel (2023)
ABSTRACT: “THE AIM OF THE PRESENT RESEARCH WORK IS TO ANALYZE THE EFFECTIVENESS OF PLATELET-RICH PLASMA (PRP) IN WOUND HEALING AFTER DENTAL EXTRACTION, AS WELL AS TO IDENTIFY ITS ADVANTAGES AND LIMITATIONS”. From the initial pool of 534 articles were collected, the criteria for selecting 86, base on their average citation count and Scimago Journal Ranking impact factor, 73 scientific articles were included, meeting the standard of an average citation count greater than 1.5 and impact factor (SJR) and Quartile (Q) rankings for the systematic review. After reviewing the literature, it was found that platelet-rich plasma(PRP) is a concentrate of the patient's autologous blood that contains growth factors, particularly PDGF and TGF-b, promotes bone regeneration, clot stability and adhesive function after dental extraction In addition, PRP has also been shown to improve clot stability and wound healing, speed up bone regeneration and increased bone density and reduce pain after the procedure, with the most significant being its high cost, would be a limitation for patients who cannot afford it.